(untitled) - Benson, Ian (London, 1983)
This book introduce social aspects of the scientific-technical revolution. A new framework for agreement: data agreements, technology agreements, a new social contract...
Keywords: Đổi mới công nghệ,Technological innovations; Khía cạnh xã hội,Social aspects